1979
DOI: 10.7326/0003-4819-90-4-538
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires' Disease in Patients with Associated Serious Disease

Abstract: Of nine patients with Legionnaires' disease, seven were receiving corticosteroids, and all nine had serious underlying diseases. Direct immunofluorescent examination of respiratory secretions, including sputum and transtracheal aspirates, showed the Legionnaires' disease (LD) bacterium in five of seven patients who seroconverted and in a sixth patient with a single elevated titer to the LD bacterium. All nine patients received erythromycin therapy, and five survived. Two patients showed persistence of their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
3

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 12 publications
0
31
0
3
Order By: Relevance
“…It is known from previous in vitro studies with and without the inclusion of macrophages that the effect of erythromycin on L. pneumophila is an inhibitory one (2,18,21,24,25,31,38). In vivo comparative drug studies of the doses and lengths of therapy needed in patients with different primary diseases are lacking (8,16,23,(28)(29)(30). Therefore, the possible use of different cell-penetrating drugs other than macrolides, i.e., rifampin or fluoroquinolones, has been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known from previous in vitro studies with and without the inclusion of macrophages that the effect of erythromycin on L. pneumophila is an inhibitory one (2,18,21,24,25,31,38). In vivo comparative drug studies of the doses and lengths of therapy needed in patients with different primary diseases are lacking (8,16,23,(28)(29)(30). Therefore, the possible use of different cell-penetrating drugs other than macrolides, i.e., rifampin or fluoroquinolones, has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect was observed only at 2.0 times the MIC of either drug. Erythromycin and ofloxacin at similar concentrations had inhibitory effects, with evidence of regrowth of the organism at 72 h. Because of the frequent addition of rifampin to patients seriously ill with infections caused by L. pneumophila, our time-kill curve studies included fluoroquinolone or erythromycin combinations with The mortality rate among patients with L. pneumophila infections continues to be high, especially in bacteremic, immunocompromised, and intubated patients (8,16,23,29). It is known from previous in vitro studies with and without the inclusion of macrophages that the effect of erythromycin on L. pneumophila is an inhibitory one (2,18,21,24,25,31,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, viral and toxic etiologies were sought, because of the clinical resemblance of the pneumonia to severe influenza. Although clinical features suggestive of Legionella infection, such as prominence of gastrointestinal and cerebral symptoms, have been described (121,156,182,231), some investigators have found it difficult to differentiate between pneumonia caused by Legionella spp. and that caused by other bacteria (186,222,279).…”
Section: Philadelphia Epidemic Of Legionnaires Diseasementioning
confidence: 99%